The Reception of Pseudo-Dionysius’s Negative Theology in Alan of Lille - Osorio, José (Revista Española de Filosofía Medieval, 2020)
The article investigates the reception of Pseudo-Dionysius’s negative theology in Alan of Lille’s philosophical and speculative theological works. In the first part, the paper discusses how Alan applied Pseudo-Dionysius’s negative theology to the problem of translatio and the limits of theological language. In the second part, the article sheds light on the problematic textual references and allusions in Alan’s appropriation and remarks about Pseudo-Dionysius. In the final section, the paper argues that despite Alan’s lack of access to the complete Corpus Aeropagiticum, his interpretation and adoption of negative theology is philosophically compelling.